2013
DOI: 10.1177/0748233713498924
|View full text |Cite
|
Sign up to set email alerts
|

Serum prolidase activity, oxidative stress, and antioxidant enzyme levels in patients with renal cell carcinoma

Abstract: Our results indicate that increased prolidase seems to be related to increased oxidative stress along with decreased antioxidant levels in renal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 45 publications
(53 reference statements)
2
14
1
1
Order By: Relevance
“…[41] Previously reported data suggest a significant decrease in the levels of anti-oxidative enzymes in serum of RCC patient. [36,42] Decreased levels of anti-oxidative enzymes (SOD, CAT, GSH and APOX) in the present finding can be a cause of progression of RCC in patients ( Figure 3). …”
Section: Discussionmentioning
confidence: 53%
“…[41] Previously reported data suggest a significant decrease in the levels of anti-oxidative enzymes in serum of RCC patient. [36,42] Decreased levels of anti-oxidative enzymes (SOD, CAT, GSH and APOX) in the present finding can be a cause of progression of RCC in patients ( Figure 3). …”
Section: Discussionmentioning
confidence: 53%
“…The results indicated that an increased prolidase activity might be related to increased oxidative stress along with decreased antioxidant levels in renal cancer (41).…”
Section: Oxidative Stress and Prolidasementioning
confidence: 90%
“…The final step of collagen degradation is catalyzed by intracellular prolidase; therefore, it may be associated with neoplastic transformation. Increased prolidase activities have been observed in some of cancers, such as lung cancer [15] , breast cancer [16] , endometrial cancer [17] , stomach cancer [18] , renal cell cancer [19] and ovarian cancer [20] . On the other hand, Palka et al [6] showed reduced levels of prolidase in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%